Stability of banking systems in BRICS countries: state vs. private bank ownership - Suchkov, Ivan (University of the Witwatersrand, Johannesburg, 2022)
In today's global business environment of cutthroat competition and continuous innovation, companies need to constantly reinvent themselves in order to stay ahead. As Arthur Martinez, Chairman and Chief Executive Officer of Sears, said just over a decade ago, "If you look at the best retailers out there, they are constantly reinventing themselves." (Greenwald, 1996, p. 54) Some 18 years ago, Jim O'Neill introduced the term “BRIC countries” (Brazil, Russia, India, and China) that ever since has been entrenched in the common language of economists around the world. At that time, the joint BRIC’s GDP in PPP terms constituted $9,668 bln. or 23.3% of world GDP (O’Neill, 2001). This club of four emerging economies that were grouped according to their economic growth potential and uprising global influence was joined by South Africa in late 2010. In the decade following the Global Financial Crisis (GFC) of 2008, the contribution of BRICS countries to world economic growth is known to have exceeded nearly 50%, and these countries will outrun the developed economies in terms of annual economic growth figures by 2030 (Kose & Ozturk, 2014). During the last two decades the trade turnover of BRICS countries has approximately tripled, which is a clear sign of an increased magnitude of their role in global trade flows (Rasoulinezhad & Jabalameli, 2018).
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Finance and Investment to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2022
Keywords: Banking stability; Banking efficiency; BRICS; Bank ownership; SDG-8: Decent work and economic growth